Predictive Factors for Recovery Time in Conceived Women Suffering From Moderate to Severe Ovarian Hyperstimulation Syndrome - Huang, Kai; Shi, Ying; Chen, Gezi; Shi, Hao; Zhai, Jun (Frontiers in Endocrinology, 2022)
Objective: To evaluate potential predictors for recovery time in pregnant patients with moderate to severe ovarian hyperstimulation syndrome. Methods: A total of 424 pregnant patients with moderate to severe OHSS underwent in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) were retrospectively identified. The clinical features and laboratory findings within 24 hours after admission were collected. Treatment of OHSS was carried out according to standard procedure including fluid replacement therapy, human albumin, aspirin, low molecular weight heparin and paracentesis if necessary. Patients were discharged from hospital when morning hematocrit was <40% and no obvious clinically relevant symptoms were existed, such as abdominal distension, abdominal pain and shortness of breath. Meanwhile, ultrasound indicated little pleural or abdominal effusion and biochemical abnormalities return to normal were required. Spearman correlation analysis was used to assess the association between blood-related parameters and recovery time. Multiple linear regression models were used to assess the relationship between clinical or laboratory parameters and recovery time. Results: The median recovery time of these patients was 11 days. In spearman correlation test, leukocyte, hemoglobin, platelets, hematocrit, creatinine, PT, Fib, D-dimer, and FDP were positively correlated with recovery time. Whereas, albumin and TT were negatively correlated with recovery time. Multiple linear regression analysis showed that polycystic ovary syndrome (PCOS), hemoglobin, platelets, albumin, and Fib significantly associated with the recovery time of OHSS patients (p = 0.023, p < 0.001, p = 0.007, p < 0.001, and p = 0.019; respectively). Conclusions: In pregnant OHSS patients, presence of PCOS and hypoalbuminemia were associated with significantly longer recovery time. Meanwhile, recovery time was longer when patients have high levels of hemoglobin, platelets and Fib.